Analysis of LDL and HDL size and number by nuclear magnetic resonance in a healthy working population: The LipoLab Study. Issue 1 (8th November 2020) - Pallarés‐Carratalá, Vicente; Quesada, Jose A.; Orozco‐Beltrán, Domingo; Amigó‐Grau, Nuria; Lopez‐Pineda, Adriana; Fernández Giménez, Antonio; Gil‐Guillén, Vicente F.; Correig, Xavier; Masana, Lluis; Monleón, Daniel; Redón, Josep; Pascual, Reyes; et al.
Abstract: Background and aim: Atherosclerosis is the underlying process in cardiovascular disease (CVD), the first cause of death in developed countries. We aimed to identify people with no known CVD and normal values of LDL‐C and HDL‐C, but with alterations in the number and size of lipoprotein particles (as measured by nuclear magnetic resonance [NMR]) and to analyse their sociodemographic, clinical and biochemical characteristics. Methods: Cross‐sectional study in occupational risks prevention centre in Castellón (Spain) in 2017 and 2018, in consecutively recruited adults (18‐65 years) with no known CVD. Sociodemographic, clinical and biochemical variables were collected. Lipid profiles were analysed (Liposcale test), along with the concentration, size and number of the main types of lipoprotein particles, determined by 2D diffusion‐ordered NMR spectroscopy. Using contingency tables, we analysed the characteristics of people with normal LDL and HDL cholesterol but abnormal levels of LDL and HDL particles. The magnitude of association between explanatory variables and abnormal levels of each kind of lipoprotein was assessed with multivariable logistic regression models. Results: Of the 400 total participants (31.3% women; age 46.4 ± 4.3 years), 169 had normal LDL and HDL cholesterol. Abnormal lipoprotein particle values depended on the subtype: prevalence of abnormal LDL levels ranged from 8.3% to 36.7%; and of HDL, from 28.4% to 42.6%. High systolic blood pressure and total cholesterol were significantly associated with abnormal LDL levels. Male sex and high systolic blood pressure were associated with abnormalities in HDL. Conclusions: An extended lipids profile, obtained by NMR, enables the identification of people with normal HDL‐C and LDL‐C levels who present abnormal levels of LDL‐P and/or HDL‐P. Higher total cholesterol, systolic blood pressure, BMI and male sex were significantly associated with these abnormal values.